The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsearthspacechem.0c00055
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Export Flux in the Arctic Ocean Estimated from 234Th/238U Disequilibria

Abstract: High mercury (Hg) levels have been observed for arctic biota despite limited local sources of anthropogenic Hg in the Arctic. Scavenging of Hg exerts an important control on the residence time of Hg in surface waters. The downward Hg export flux, as well as Hg burial rates in bottom sediments, are not well constrained due to the lack of particulate Hg (pHg) observations in the Arctic Ocean. Here we estimated downward Hg export flux based on Hg concentrations in suspended particulate matter (SPM) and by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…When integrated across zones, our estimate provides nearly full coverage of the Arctic Ocean deeper than 1,000 m (Figure 8c and Figure S11). The integrated Arctic Hg flux is 4.4 ± 0.7 Mg/yr, which is consistent with a recent estimate in the deep Arctic (4 ± 3 Mg/yr) that derived fluxes by assuming a constant sedimentation rate (Tesán Onrubia et al., 2020). The uncertainty in our flux estimate is a minimum as it only accounts for uncertainty in the Th‐normalized flux interpolation.…”
Section: Resultssupporting
confidence: 90%
“…When integrated across zones, our estimate provides nearly full coverage of the Arctic Ocean deeper than 1,000 m (Figure 8c and Figure S11). The integrated Arctic Hg flux is 4.4 ± 0.7 Mg/yr, which is consistent with a recent estimate in the deep Arctic (4 ± 3 Mg/yr) that derived fluxes by assuming a constant sedimentation rate (Tesán Onrubia et al., 2020). The uncertainty in our flux estimate is a minimum as it only accounts for uncertainty in the Th‐normalized flux interpolation.…”
Section: Resultssupporting
confidence: 90%
“…This is while the scavenged Hg by productivity-related particles in the water column is buried more rapidly in sediments. The scavenging of Hg has an important control on the residence time of Hg waters (Tesán Onrubia et al, 2020). This phenomenon facilitates the downward flux of Hg to the seafloor which could be slow otherwise.…”
Section: Comparison Of Hg Accumulation In the Three Coresmentioning
confidence: 99%
“…At present, the global burial flux for Hg in ocean sediments is not very well-constrained but likely lies between the value of 1.2 µg m −2 y −1 in open ocean conditions and 1,200 µg m −2 y −1 in hyper-accumulating regions like the Antarctic margin (Soerensen et al, 2016;Zaferani et al, 2018). Models have suggested that the global burial flux falls between 1.7 and 7 µg m −2 y −1 (e.g., Outridge et al, 2018;Tesán Onrubia et al, 2020). Given the current oceanic inventory of Hg, these burial fluxes suggest a residence time of Hg of about 520 years (Outridge et al, 2018).…”
Section: Introductionmentioning
confidence: 98%